Notes on governance and planning in the Metropolitan Region of Sorocaba (São Paulo - Brazil) - Santana-Chaves, Igor Matheus; Leonel, Ana Lia; Anjos, Lidiane Alonso Paixão dos; Momm, Sandra; Catelan, Márcio José; Frey, Klaus (Faculdade de Ciências e Letras - Unesp - Araraquara., 2022)
The article contributes to the discussion on transformations of structures and practices of governance and planning in metropolitan areas, taking as a cutout the case of the institutional formation of the Metropolitan Region of Sorocaba (RM-Sorocaba). To this end, through a deductive-inductive dialogue, we start with the discussion on governance and planning themes in order to understand the metropolitan issue in Brazil, and appropriates the case with documentary analysis. The analysis and discussion involves different proposals of municipal grouping in the last 20 years and the institutional constitution of the RM-Sorocaba and its agency. From the analysis and the literature review, possible institutional strategies are discussed in order to collaborate with research, activities and plans for the RM-Sorocaba, with a view to promoting more interactive and democratic political practices between the different levels of governance in which it is established. Challenges for the creation of the Plan for the Integrated Urban Development of the Metropolitan Region of Sorocaba (PDUI-RM-Sorocaba) are pointed out, considering public participation and the obstacles of multiscale governance, due to the technical-bureaucratic and rationalist legacy of the state planning model. Finally, the article contributes on historical processes of territorial formation and their effects on the currently institutionalized governance systems and their effectiveness for planning integration in metropolises.